The Role of Continuous Auditing in Enhancing Corporate Governance - Mudawanah, Siti; Fatimah, Imas; Nalsal, Pindonta; Purnomo, Adi Dwi (Islamic Studies in the World, 2024)
Background. Continuous auditing has emerged as a valuable tool in strengthening corporate governance, providing real-time monitoring and assessment of financial and operational activities within organizations. The shift towards continuous auditing reflects the need for more proactive and transparent governance practices, allowing companies to detect irregularities and mitigate risks in a timely manner. Purpose. This study examines the role of continuous auditing in enhancing corporate governance by analyzing its impact on risk management, compliance, and financial reporting accuracy. The primary objective is to assess whether continuous auditing can improve the effectiveness of governance structures and support organizational accountability. Method. A mixed-methods research design was employed, combining quantitative analysis of governance metrics from companies implementing continuous auditing with qualitative insights from interviews with auditors and corporate governance experts. Data was gathered on key performance indicators, including error reduction, compliance rates, and response times to identified risks. Results. Findings indicate that continuous auditing significantly enhances governance outcomes, with a 40% reduction in errors and a 30% increase in compliance adherence. Qualitative feedback supports these results, highlighting the increased transparency and accountability that continuous auditing fosters within organizations. Conclusion. The study concludes that continuous auditing is an essential component of effective corporate governance, allowing companies to respond proactively to risks and maintain high standards of compliance. As companies continue to navigate complex regulatory environments, continuous auditing offers a strategic advantage, ensuring sustained organizational integrity and stakeholder trust. Embracing continuous auditing can therefore contribute to a more robust governance framework, reinforcing ethical practices and fostering long-term organizational resilience.